Disrupted relationship between blood glucose and brain dopamine D2/3 receptor binding in patients with first-episode schizophrenia - U. Sauerzopf; A. Weidenauer; I. Dajic; M. Bauer; L. Bartova; B. Meyer; L. Nics; C. Philippe; S. Pfaff; V. Pichler; M. Mitterhauser; W. Wadsak; et al. (NeuroImage: Clinical, 2021)
An elemental function of brain dopamine is to coordinate cognitive and motor resources for successful exploitation of environmental energy sources. Dopamine transmission, goal-directed behavior, and glucose homeostasis are altered in schizophrenia patients prior to and after initiation of pharmacological treatment. Thus, we investigated the relationship between blood glucose levels and brain dopamine signaling in drug-naïve patients with first-episode psychosis.We quantified blood glucose levels and binding of the dopamine D2/3 receptor agonist radioligand (+)-[11C]-PHNO in 15 medication-naïve patients and 27 healthy volunteers employing positron emission tomography.Whole-brain voxel-wise linear model analysis identified two clusters of significant interaction between blood glucose levels and diagnosis on (+)-[11C]-PHNO binding-potential values. We observed positive relationships between blood glucose levels and binding-potential values in healthy volunteers but negative ones in patients with first episode psychosis in a cluster surviving rigorous multiple testing correction located in the in the right ventral tegmental area. Another cluster of homologous behavior, however at a lower level of statistical significance, comprised the ventral striatum and pallidum. Extracellular dopamine levels are a major determinant of (+)-[11C]-PHNO binding in the brain. In line with the concept that increased dopamine signaling occurs when goal-directed behavior is needed for restoring energy supply, our data indicate that in healthy volunteers, extracellular dopamine levels are high when blood glucose levels are low and vice-versa. This relationship is reversed in patients with first-episode psychosis, possibly reflecting an underlying pathogenic alteration that links two seemingly unrelated aspects of the illness: altered dopamine signaling and dysfunctional glucose homeostasis.